Construction of Educational Objectives: An Analysis from Blooms Perspectives (Pragyaratna प्रज्ञारत्न, 2023)
The purpose of this study was to create educational objectives based on different levels of the cognitive domain of Bloom's taxonomy. Moreover, it aimed to identify the action verbs related to science education at the secondary level for bachelor-level students. To achieve this, a qualitative research methodology was used with 15 students selected through a purposive sampling procedure from campus A. In-depth interview guidelines and focus group discussions were prepared and validated by subject experts and colleagues. Seven students participated in the interview, and two FGDs were conducted using the research tools. The field data was coded and analyzed thematically. The study investigates the difficulties of Bloom's Taxonomy and its application in modern education and cognitive science. It also identifies the action verbs and their possible specific and behavioral objectives in science education. Each level of cognitive domain emphasizes its significance in curriculum building, instructional strategies, and assessing cognitive growth in science education. The research investigates the changing applications of Bloom's Taxonomy that should be used in today's technologically driven educational context.